Towards a better understanding of Apis mellifera and Varroa destructor microbiomes: introducing 'phyloh' as a novel phylogenetic diversity analysis tool. (19th November 2014) - Sandionigi, A.; Vicario, S.; Prosdocimi, E. M.; Galimberti, A.; Ferri, E.; Bruno, A.; Balech, B.; Mezzasalma, V.; Casiraghi, M.
Abstract The study of diversity in biological communities is an intriguing field. Huge amount of data are nowadays available (provided by the innovative DNA sequencing techniques), and management, analysis and display of results are not trivial. Here, we propose for the first time the use of phylogenetic entropy as a measure of bacterial diversity in studies of microbial community structure. We then compared our new method (i.e. the web tool phyloh) for partitioning phylogenetic diversity with the traditional approach in diversity analyses of bacteria communities. We tested phyloh to characterize microbiome in the honeybee (Apis mellifera, Insecta: Hymenoptera) and its parasitic mite varroa (Varroa destructor, Arachnida: Parasitiformes). The rationale is that the comparative analysis of honeybee and varroa microbiomes could open new perspectives concerning the role of the parasites on honeybee colonies health. Our results showed a dramatic change of the honeybee microbiome when varroa occurs, suggesting that this parasite is able to influence host microbiome. Among the different approaches used, only the entropy method, in conjunction with phylogenetic constraint as implemented in phyloh, was able to discriminate varroa microbiome from that of parasitized honeybees. In conclusion, we foresee that the use of phylogenetic entropy could become a new standard in the analyses of community structure, in particular to prove the contribution of each biological entity to the overall diversity.